Case Report: Infant-onset Degos disease with nervous system involvement and a literature review - Shi, Xin-Wei; Deng, Jiang-Hong; Li, Cai-Feng (Frontiers in Pediatrics, 2024)
Abstract：Degos disease also known as malignant atrophic papulosis (MAP), is an autoinflammatory disease that mainly affects small- to medium-sized arteries. Gastrointestinal and nervous system are most commonly affected systems. Herein, we reported a case of Degos disease with disease onset during infantile and had severe neurological involvement.